Model Teaching Factory (TEFA) Sebagai Strategi Peningkatan Nilai Tambah Peternak Sapi Perah di Jember - Irnawati, Irnawati; Fatmawati, Yuni; Mudakir, Imam; Asyiah, Iis Nur (Universitas Galuh, 2025)
The potential of dairy farming in Jember Regency is enormous, but the added value of milk products is still low because farmers sell raw milk without further processing. This study aims to analyze the potential replication of the Teaching Factory (TEFA) model of Jember State Polytechnic to increase the added value of dairy farmers. The research method uses a qualitative descriptive approach with direct observation to TEFA, literature studies, and secondary data analysis. The results showed that the TEFA model integrates dairy cattle breeding with independent feed production, waste utilization into biogas, and market-oriented milk product diversification. Bestcow Farm Jember data shows farming business has R/C Ratio of 1.09 with profit of Rp. 88,084,392.86 per year, but vulnerable to 15% feed cost increases. TEFA model replication has potential to increase added value through processed milk product diversification (30-70% margin), feed efficiency (20-30%), and waste utilization. Challenges of limited capital, human resources, and technology can be overcome through training, mentoring, and strategic partnerships. The TEFA model shows ideal agroindustrial integration with potential to increase farmer income by 100-180%.